Advanced agro-engineering technologies for rural business development - Kharchenko, Valeriy 1938-; Vasant, Pandian 1961- (IGI Global, Disseminator of Knowledge, 2019)
"This book explores a series of technological methods and a number of technical means that ensure the organization of production of various products in the territories newly allocated for economic activity. The specified technologies and technical means are adapted to applications in the production of small scale and the enterprises of small and medium business"...
Includes bibliographical references and index
Keywords: Agricultural development projects; Rural development projects; Agricultural engineering; Agriculture -- Economic aspects